2021
DOI: 10.47626/2237-6089-2021-0251
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences in patients with psoriasis

Abstract: Introduction Adverse childhood experiences (ACEs) have been linked to occurrence of autoimmune diseases in adults, including psoriasis. Objectives To study the prevalence of ACEs in psoriasis patients, comparing them with a sample from the general population. Methods Three hundred and eighteen individuals were included (104 psoriasis patients and 214 controls). Patients and controls answered questions on an ACE study questionnaire about exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Researchers had previously found that ACEs were associated with an increased chance of development of obesity in adulthood 8 as well as development of other chronic health conditions such as high blood pressure, 9 diabetes, 5,10 atopic dermatitis, 11 and psoriasis. 12 While a direct mechanism of association has not been determined for these conditions, different biological pathways have been proposed to explain this phenomenon. One pathway suggests that ACEs cause a change in epigenetic mechanisms to the immune system, which may ultimately predispose patients exposed to ACEs to illness as well as chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers had previously found that ACEs were associated with an increased chance of development of obesity in adulthood 8 as well as development of other chronic health conditions such as high blood pressure, 9 diabetes, 5,10 atopic dermatitis, 11 and psoriasis. 12 While a direct mechanism of association has not been determined for these conditions, different biological pathways have been proposed to explain this phenomenon. One pathway suggests that ACEs cause a change in epigenetic mechanisms to the immune system, which may ultimately predispose patients exposed to ACEs to illness as well as chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Adult obesity [67] Adverse childhood event Arterial stiffness Cardiovascular Disease [68] Adverse childhood experiences Female psoriasis patients had more ACEs than controls or male patients. Psoriasis [69] Adverse childhood experiences Evaluated in adulthood and specifically associated with other ACE comorbidities (e.g., depression).…”
Section: Period Of Early Life Biomarkers (Population Subset) Ncd/cd E...mentioning
confidence: 99%